Simultaneous removal of methyl parathion and chlorpyrifos pesticides from model wastewater using coagulation/flocculation: Central composite design - Saini R.; Kumar P. (My University, 2025)
Removal of common pesticides methyl parathion and chlorpyrios was investigated through coagulation/flocculation using two commercial coagulants alum [Al2(SO4)3·18H2O] and ferric chloride (FeCl3). The removal efficiency of both pesticides was evaluated by varying the initial pH (4-9), coagulant dose (20-120 mg/L) and coagulant type. Response surface methodology (RSM) was used to design the jar-test experiments and central composite design (CCD) was used to analyze the effects of initial pH and coagulant on COD and pesticide removal. The most significant effect on removal efficiency was observed with FeCl3. Optimum dose of alum and ferric chloride was found to be 80 and 60 mg/L, respectively. The maximum concentration removal was 79% for methyl parathion and 82% for chlorpyrifos solution, respectively. The results demonstrated that FeCl3 caused higher removal compared to alum. © 2015 Elsevier Ltd. All rights reserved.